Biocompatible Reactive Oxygen Species (ROS)‐Responsive Nanoparticles as Superior Drug Delivery Vehicles. Issue 1 (22nd August 2014) - Zhang, Dinglin; Wei, Yanling; Chen, Kai; Zhang, Xiangjun; Xu, Xiaoqiu; Shi, Qing; Han, Songling; Chen, Xin; Gong, Hao; Li, Xiaohui; Zhang, Jianxiang
<x xml:space="preserve">Abstract</x> A novel reactive oxygen species (ROS)‐responsive nanoplatform can be successfully manufactured from a ROS‐triggerable β‐cyclodextrin material. Extensive in vitro and in vivo studies validate that this nanoscaled system may serve as a new drug delivery vehicle with well‐defined ROS‐sensitivity and superior biocompatibility. This nanocarrier can be used for ROS‐triggered transport of diverse therapeutics and imaging agents. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>